Como as famílias brasileiras avaliam a suficiência de seus rendimentos segundo a POF 2002-2003: Implicaç\~oes para um índice de qualidade de vida - Marcelo de Sales Pessoa; Marcos Antonio Coutinho da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The work investigates the demographic, economic and social determinants of the degree of satisfaction of the Brazilian househols with their income. For that, a ordered logit model is estimated in order to explain the performance of a subjective indicator of income sufficiency built with basis on the POF 2002-2003 survey on Life Conditions Evaluation. Despite the expressive marginal effect of the current income and the consumption on the indicator, the low joint explanation power of these variables is consistent with the well documented empirical evidence of a mismatch between objective and subjective indicators of life quality, at least regarding the material domains of human existence. This result can be explained to some extent by differences in expectations and relative income perception among Brazilian households. The inclusion of an exhaustive number of explanatory variables into the regression improves the model significantly, although to an insufficient extent to produce a satisfactory adjustment to the data. This suggests the existence of some type of non-observed heterogeneity explaining a considerable proportion of the variation of the degree of satisfaction of the Brazilian househols with their income. Another important result of the work is that the marginal effect of permanent shocks to current income on the indicator of income sufficiency is stronger that the effect of transitory shocks to current income.
Keywords: I30; I31; I39; 330; Haushaltseinkommen; Zufriedenheit; Brasilien